Algebra 2 (1st Edition)

Published by McDougal Littell
ISBN 10: 0618595414
ISBN 13: 978-0-61859-541-9

Chapter 12 Sequences and Series - 12.4 Find Sums of Infinite Geometric Series - 12.4 Exercises - Mixed Review - Page 825: 53



Work Step by Step

Here, we have $a_n= a_1r^{(n-1)}$ for the Geometric series. We are told that $a_2=-18$ and $r=-3$ Here, we have $a_2=(a_1) \times (-3)^{(2-1)} \implies -18=(a_1) \times (-3)$ or, $a_1=6$ Now, $a_n=a_1 \times r^{n-1}$ Hence, $a_n=6(-3)^{n-1}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.